FT-IR Analysis of Urinary Stones: A Helpful Tool for Clinician Comparison with the Chemical Spot Test. (26th April 2014) - Primiano, Aniello; Persichilli, Silvia; Gambaro, Giovanni; Ferraro, Pietro Manuel; D'Addessi, Alessandro; Cocci, Andrea; Schiattarella, Arcangelo; Zuppi, Cecilia; Gervasoni, Jacopo
Abstract : Background. Kidney stones are a common illness with multifactorial etiopathogenesis. The determination of crystalline and molecular composition and the quantification of all stone components are important to establish the etiology of stones disease but it is often laborious to obtain using the chemical method. The aim of this paper is to compare chemical spot test with FT-IR spectroscopy, for a possible introduction in our laboratory. Methods. We analyzed 48 calculi using Urinary Calculi Analysis kit in accordance with the manufacturer's instructions. The same samples were analyzed by FT-IR using the Perkin Elmer Spectrum One FT-IR Spectrometer. All FT-IR spectra of kidney stones were then computer matched against a library of spectra to generate a report on the various components. Results. On the basis of FT-IR analysis, the 48 calculi were divided into three groups: pure stone, mixed stone, and pure stone with substances in trace. Results of each group were compared with those obtained with chemical spot test. A general disagreement between methods was observed. Conclusions. According to our data, the introduction of the FT-IR technique in clinical chemistry laboratory may be more responsive to clinician expectations.